The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201405932
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Tuned Electron Transfer and Electrocatalysis of Hexameric Tyrosine‐Coordinated Heme Protein

Abstract: Molecular modeling, electrochemical methods, and quartz crystal microbalance were used to characterize immobilized hexameric tyrosine-coordinated heme protein (HTHP) on bare carbon or on gold electrodes modified with positively and negatively charged self-assembled monolayers (SAMs), respectively. HTHP binds to the positively charged surface but no direct electron transfer (DET) is found due to the long distance of the active sites from the electrode surfaces. At carboxyl-terminated surfaces, the neutrally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…Modeling studies highlight the crucial role played by the surface charge for effective reactions at the interface. For example, the hexameric tyrosine coordinated protein (HTHP) will adsorb in a nonproductive orientation for DET on positively charged SAMs [174]. In their work on sulfite oxidase adsorbing on SAMs, Utesch et al showed how the solution ionic strength impacts the enzyme adsorption [175].…”
Section: Importance Of Electrostatic Interactions To Drive the Orientmentioning
confidence: 99%
“…Modeling studies highlight the crucial role played by the surface charge for effective reactions at the interface. For example, the hexameric tyrosine coordinated protein (HTHP) will adsorb in a nonproductive orientation for DET on positively charged SAMs [174]. In their work on sulfite oxidase adsorbing on SAMs, Utesch et al showed how the solution ionic strength impacts the enzyme adsorption [175].…”
Section: Importance Of Electrostatic Interactions To Drive the Orientmentioning
confidence: 99%
“…16,17 It has been proposed that mesoporous structures with porous radii close to the radius of an enzyme [18][19][20] and electrostatic interaction between the redox center of an enzyme and an electrode surface [21][22][23][24][25][26] are important to improve the performance of DET-type bioelectrocatalysis. Therefore, there seems to be some possibility to construct mesoporous electrodes suitable for DET reaction of POD.…”
Section: Introductionmentioning
confidence: 99%
“…Although some suitable redox mediators may assist electron transfer [34,35], several drawbacks arise [1-4, 10, 34, 35]: (a) the toxicity of the mediator, (b) leakage of the mediator, and (c) cell voltage loss to set up the driving force in the electron transfer between the enzyme and mediator. Therefore, multiple studies, such as creating novel electrode materials [36][37][38][39][40][41][42], functionalizing electrode surface [9,[43][44][45][46][47][48][49][50][51], and protein engineering [52][53][54], to improve DET-type bioelectrocatalysis have been reported.…”
Section: Introductionmentioning
confidence: 99%